2010
DOI: 10.1039/c004658b
|View full text |Cite
|
Sign up to set email alerts
|

An automated microfluidic platform for calcium imaging of chemosensory neurons in Caenorhabditis elegans

Abstract: Functional fluorescence imaging methods are widely used to study cellular physiology. When applied to small organisms, these methods suffer from low-throughput due to the laborious immobilization/stimulus delivery procedure that is typically involved during imaging. Here, we describe the development of an automated microfluidic-based platform for performing automated neuronal functional (calcium) imaging in the roundworm Caenorhabditis elegans. The platform, capable of processing tens to hundreds of worms per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 36 publications
2
110
1
Order By: Relevance
“…Combined with fluorescence imaging of calcium transmitters and neurons, behavior mechanism could be explored in the neuronal level [60]. Based on the established microfluidic devices by several researchers, accurate stimuli could be delivered to individual worms flexibly and responses of worms behavior and neuron could be monitored [33,35,39,52,[61][62][63][64].…”
Section: Neuron Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…Combined with fluorescence imaging of calcium transmitters and neurons, behavior mechanism could be explored in the neuronal level [60]. Based on the established microfluidic devices by several researchers, accurate stimuli could be delivered to individual worms flexibly and responses of worms behavior and neuron could be monitored [33,35,39,52,[61][62][63][64].…”
Section: Neuron Activitymentioning
confidence: 99%
“…Chung and others [29] used the cooperation of a cooler and micro-valves to restrict the movement of C. elegans, and exploited software to realize automatic images identification and [52]; (b) a microfluidic platform enabled stable worm immobilizaton for axotomy and observation of neural regeneration process [27]. cell ablation.…”
Section: Neuron Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronis et al also demonstrated the ability to deliver the odors with precise temporal control while monitoring the neuronal activity, which is difficult with conventional imaging techniques. Upgraded versions of this design can now be used for the automation of the process from worm loading to image acquisition increasing the throughput up to 30 worms/h, 26 and the ability of delivering multiple chemical stimuli in specific temporal patterns. 27 These chips have had a great impact on calcium imaging experiments particularly in the dissection of the olfactory behavior circuitry.…”
Section: B Neural Functional Imaging and Optical Manipulationmentioning
confidence: 99%